EFFECT OF EMOTIONAL INTELLIGENCE AND TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS INTERVENING VARIABLE - Dwi Nuriyani; Muhammad Arif (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to find out and analyze several things, namely; the influence of emotional intelligence on organizational commitment, the influence of transformational leadership on organizational commitment, the influence of emotional intelligence on job satisfaction, the influence of transformational leadership on job satisfaction, the influence of job satisfaction on organizational commitment. The influence of emotional intelligence on organizational commitment mediated by job satisfaction and the influence of transformational leadership on organizational commitment mediated by job satisfaction. In this study, it used an associative type of research with a sample of 54 respondents who were employees of the Perum Bulog Medan Branch Office. The data collection technique used a list of statements such as questionnaires and data analysis techniques using Partial Least Square (SmartPls) to test the seven hypotheses proposed in this study. The results of the research showed that the influence of emotional intelligence on organizational commitment was positive and significant, there was no influence of transformational leadership on organizational commitment, the influence of emotional intelligence on job satisfaction was positive and significant, the influence of transformational leadership on job satisfaction was positive and significant, the effect of job satisfaction on organizational commitment is positive and significant, there is no influence of emotional intelligence on organizational commitment through job satisfaction (meaning that job satisfaction does not become a mediating variable between emotional intelligence and organizational commitment), the influence of transformational leadership to employee performance mediated by positive and significant job satisfaction (meaning that job satisfaction becomes a mediating variable between transformational leadership and organizational commitment).